Handbook of motivation at school [ - Wentzel, Kathryn R.; Wigfield, Allan (Educational psychology handbook series, 2009)
A comprehensive and integrated compilation of theory and research on children's motivation at school. It covers the major theoretical perspectives in the field as well as their application to